Extent of sewage pollution in coastal environment of Mumbai, India: an object‐based image analysis. (6th April 2015) - Vijay, Ritesh; Kushwaha, Vikash K.; Pandey, Neha; Nandy, Tapas; Wate, S. R.
Abstract The coastal water quality of Mumbai is deteriorating by receiving partially treated effluent from wastewater treatment facilities, sewage discharges from ocean outfalls and discharges from point and non‐point sources in the creek and coast. A novel approach of object‐based image analysis has been used in this research study to assess the extent of sewage pollution in the coastal environment of Mumbai. For this, Indian Remote Sensing P6 Linear Imaging Self Scanning IV image was used for multiresolution segmentation and rule‐based image classification as per normalised difference water index and normalised difference turbidity index. Water quality regions as per classification were strongly correlated with observed water quality parameters. Based on classified regions and water quality parameters, extent of sewage pollution in the coast was ranked from high to least polluted. The approach developed in this methodology should be tested in similarly polluted waters to ascertain its adaptability for assessing the spatial extent of sewage pollution.